Bit by Bit. Issue 4 (April 2018) - Unknown
Abstract : In many ways, this book has been overtaken by events. The controversies swirling around Facebook and Cambridge Analytica, among others, are likely to change forever our attitudes to the exploitation of data gathered via social networks and other tech platforms.